2014
DOI: 10.1302/0301-620x.96b7.32894
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of proximal humeral fractures in the elderly

Abstract: This study describes the epidemiology and outcome of 637 proximal humeral fractures in 629 elderly (≥ 65 years old) patients. Most were either minimally displaced (n = 278, 44%) or two-part fractures (n = 250, 39%) that predominantly occurred in women (n = 525, 82%) after a simple fall (n = 604, 95%), who lived independently in their own home (n = 560, 88%), and one in ten sustained a concomitant fracture (n = 76, 11.9%). The rate of mortality at one year was 10%, with the only independent predictor of surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
3
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 26 publications
2
72
3
4
Order By: Relevance
“…Previously, it has been reported that elderly women who sustain proximal humerus fractures tend to live independently in their own houses. Together with the seasonal variation that is observed, this may suggest that proximal humerus fracture patients tend to be more active and ambulatory than hip fracture patients [17].…”
Section: Discussionmentioning
confidence: 95%
“…Previously, it has been reported that elderly women who sustain proximal humerus fractures tend to live independently in their own houses. Together with the seasonal variation that is observed, this may suggest that proximal humerus fracture patients tend to be more active and ambulatory than hip fracture patients [17].…”
Section: Discussionmentioning
confidence: 95%
“…showering and dressing), or a focus on concomitant mobility problems, may be overlooked in the busy ED environment. Consideration should also be given to the impact that immobilising proximal humeral fractures will have on the patient's functional outcomes in the context of social independence, returning to their own home, participation in recreational activities, doing the shopping or dressing themselves . These social aspects are often more predictive of outcome than the severity of fracture, and as such, referrals to the multi‐disciplinary team within the ED should be considered to promote a safe discharge home and improved patient outcomes for more vulnerable adults.…”
Section: Discussionmentioning
confidence: 99%
“…Proximal humeral fractures in the elderly have a poor outcome, and open reduction with locking plate osteosynthesis accounts for substantial complication rates that range from 49% [12]up to 76% [28-32], with secondary dislocation/cutting out as one major problem [33]. Although intraoperative failures are frequently preventable [34], postoperative X-rays are often difficult to evaluate, and comparison remains challenging [13, 35, 36], especially because missing cortical support causes a poor outcome [37].…”
Section: Discussionmentioning
confidence: 99%